Tourism in a transforming wold economy and the impacts of the brave new world : how might developing nations achieve long-term sustainable development. - Clayton, Anthony (Worldwide Hospitality and Tourism Themes: Volume 6, Issue 2., 2014)
This e-book investigates the implications of evolving patterns of travel annd tourism for developing nations. It addresses the changes that are occurring (social, economic, technological and environmental) which raise important questions as to how small, relatively vulnerable nations can respond, especially when they have little or no control over most of the relevant variables. Specifically, what are implications for emerging economies and for tourism-dependent developing economies.